Pedagogical Innovation, Educational Management Efficiency, Stakeholder Collaboration - Budi Santoso; Kholil Bisyri (proceedings.icesy, 2026)
This study aims to analyze how pedagogical innovation can act as a catalyst in improving the efficiency of education financing management at SMP Plus Darussalam Blokagung. This study uses a qualitative approach with a case study design to analyze the role of pedagogical innovation in the efficiency of financing management at SMP Plus Darussalam Blokagung. Data were collected through in-depth interviews with the principal, teachers, administrative staff, and parents, classroom observations, and analysis of supporting documents such as budget plans and financial reports. Data analysis was conducted inductively, including reduction, presentation, and conclusion drawing, so that the relationship between pedagogical innovation, technology, and financial management could be revealed contextually and systematically, while also providing recommendations for adaptive and efficient education strategies. The results of this study indicate that pedagogical innovation, technology integration, and stakeholder collaboration simultaneously play an important role in improving the efficiency of education financing management at SMP Plus Darussalam Blokagung. Project-based learning methods and digital teaching materials optimize resources, while technology facilitates real-time, transparent, and accountable budget monitoring. Collaboration between the principal, teachers, and parents supports targeted budget planning and the implementation of learning innovations. These findings confirm that innovative, adaptive, and collaborative educational strategies not only improve the efficiency and quality of learning but also strengthen the school's operational sustainability.